Energy balance study for 4 stroke gasoline engine analyses - Abdullah Shariffudin, Mohamad (2009)
This thesis focuses on a comparative energy balance study based on a four cylinder gasoline engine data operated on different engine speed of wide open throttle. The key objective of conducting the energy balance study is to determine the most influence factor that contribute to the heat losses. The transfer of energy was measured for losses to the engine coolant and exhaust, usable power output, as well as friction losses. In a conventional internal combustion engine, approximately one-third of total fuel input energy is converted to useful work. A major part of the energy is lost with the exhaust gases. In addition, another major part of energy input is rejected in the form of heat via the cooling system. The importance of this study is to identify the key factor that contribute to the heat losses which further can be use to minimize the heat losses and at the same time improves the power output and mechanical efficiency. In present study, heat balance has been investigated theoretically for different engines speeds and load. To analyze energy balance, a zero-dimensional multi-zone thermodynamics model has been developed and used. The results showed that input energy at low engine speed was distributed 6.95%, 21.66%, 20.30%, and 0.88% to the major areas of coolant, exhaust, and power output, and friction, respectively. Differently the input energy at high engine speed was distributed 22.09%, 26.6%, 30.09%, and 5.68% to the major areas of coolant, exhaust, power output, and friction respectively. Energy loss increases with increasing engines speed and load and thus the mechanical efficiency decreases. Future improvements to obtain distinguishable results are outlined.